Faktor-Faktor Yang Mempengaruhi Kualitas Laporan Keuangan Pada Pemerintah Desa Di Kecamatan Bissappu Kabupaten Bantaeng - Djamali, Hisnol (Insan Cita Bongaya Research Journal, 2022)
The purpose of the study was to examine the factors that influence the quality of the village government's financial reports in Bissappu District, Bantaeng Regency. The population in this study were 65 village officials, Bissappu District, Bantaeng Regency. The sample technique used saturated sampling so that the sample was 65 village officials. The method of analysis is multiple linear regression analysis. The results of the study show that the village financial system and internal control system have a significant positive effect on the quality of village government financial reports